Preparation and Formation Mechanism of Electrospun Porous Beaded Fibers. Issue 3 (May 2022) - Liu, Kai; Zheng, Yuansheng; Ge, Cheng; Xin, Binjie; Dong, Xuan
Electrospun porous beaded fibers show great potential in the industrial application of many different fields; in addition, the processing parameters play an extremely important role in producing the required porous beaded fibers. In this study, polystyrene porous beaded fibers were fabricated via the electrospinning method. To further research into the formation mechanism of the electrospun porous beaded fiber, the influences of both flow rate and applied voltage on the jet motion and surface morphology of polystyrene porous beaded fibers were investigated in a systematic and comprehensive way. Images of jet trajectories and fiber morphologies under selected parameters were captured by high-speed photography and scanning electron microscopy, respectively, to explore the formation mechanism of porous beaded fibers. The experimental results showed that both flow rate and applied voltage have tremendous influence on the jet pattern and resultant fiber morphology, namely, the higher flow rate results in a multi-jet pattern and larger bead diameter, and the larger applied voltage leads to multi-jet trajectory and a reduction in the number and diameter of beads.